Unexpected Laureate: Louise Glück in Lithuania - Užgiris, Rimas (Vertimo studijos, 2020)
The aim of this paper is to give an overview of the work of the American poet, Louise Glück, winner of the 2020 Nobel Prize in Literature, with a discussion of what kinds of challenges her poetry might pose for translators. Very few people knew of her work in Lithuania prior to the Nobel Committee’s announcement. Her poems were only published in Lithuanian translation for the first time in July, 2020, and only a handful at that. This paper argues that her work has important similarities and differences to Lithuanian poetry of the twentieth century, and that despite her free-verse lyrics written in rather plain diction, there are still many challenges to rendering her work in another language. The Lithuanian translations reveal stumbling points over ambivalent word choices, surreal imagery caused by ambiguous syntax, and the need for careful attention to the tone of the narrative voice (the lyrical subject) of the poems.